Pola Asuh Orang Tua dalam Kepribadian Anak di PAUD Baburrahmah Dusun Penandak Desa Pengkelak Mas: Parenting Patterns in Children's Personalities at Baburrahmah PAUD, Penandak Hamlet, Pengkelak Mas Village - Lalu. A. Hery Qusyairi (Al-Faiza : Journal of Islamic Education Studies, 2025)
Parental care is very important for children and will affect the child's life until he/she is an adult. Therefore, parents should pay attention to choosing the right parenting pattern so the child has a good personality. This study aims to: 1) Want to know the influence of parenting patterns on children's personalities in PAUD Baburrahmah Dusun Penandak Pengkelak Mas Village? 3) Want to know the personality of children in PAUD Baburrahmah Dusun Penandak Pengkelak Mas Village? This study is a qualitative study with a qualitative descriptive approach, namely presentation in written form and explaining as it is according to the actual situation in the field. The results of this study indicate that the types of parenting patterns applied by parents in PAUD Baburrahmah Dusun Penandak Pengkelak Mas Village are Democratic parenting and Permissive parenting. The influence of Democratic parenting on children's personalities is that it can form good children's personalities, including discipline, sociability, sharing, respecting friends, and being responsible. Meanwhile, Permissive parenting can form a child's personality that is not good, for example, the child likes to disturb friends, is difficult to manage, wants to win by himself, is irresponsible, and lacks discipline. Meanwhile, the personality of children at PAUD Baburrahmah, Dusun Penandak, Pengkelak Mas Village, which totals 34 children, 30 of them already have good personalities, but 4 of them do not have good personalities.